Advances in intravesical therapy for bladder pain syndrome (BPS)/interstitial cystitis (IC). Issue 1 (17th January 2018) - Meng, En; Hsu, Yu‐Chao; Chuang, Yao‐Chi
Abstract : Bladder pain syndrome (BPS)/interstitial cystitis (IC) is a chronic symptom complex that may cause bothersome storage symptoms and pain or discomfort of the bladder, adversely affecting a patient's quality of life. The etiology of IC/BPS remains unclear, and its cause may be multifactorial. Diagnosis of IC/BPS is based on clinical features, and the possibility of other conditions must be ruled out first. Although no definitive treatment is currently available for IC/BPS, various intravesical therapies are used for IC/BPS, including heparin, hyaluronic acid, chondroitin sulfate, pentosan polysulfate, dimethylsulfoxide, liposomes, and botulinum onabotulinumtoxinA (BoNT‐A). This review summarizes the intravesical therapy for IC/BPS and discusses recent advances in the instillation of liposomal‐mediated BoNT‐A and other newly developed intravesical therapies.